Community-Based Management: Marine Tourism Development for Ecological and Economic Sustainability - Dharma Kuba; Muhammad Zulikhroom D. Kuba; Usman, Khairul Sani; Wasilah (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study analyzes community-based management approaches in the Kapoposang Marine Nature Tourism Park (TWAL) as a model for sustainable tourism development. The research examines how local community involvement in managing marine tourism areas enhances economic, social, and ecological sustainability. Using a mixed-method approach, the study combines qualitative and quantitative data, including interviews with stakeholders, direct observations, and surveys of local residents and tourists. Findings reveal that participatory approaches significantly enhance the effectiveness of marine ecosystem management, particularly in coral reef conservation, while also contributing to increased local income. However, challenges remain, particularly in infrastructure development, which limits tourism growth and local benefits. The study suggests strategies for maximizing Kapoposang's tourism potential through inclusive community engagement, addressing infrastructure gaps, and promoting sustainable practices. These insights offer valuable guidance for policymakers aiming to foster sustainable marine tourism and community empowerment in protected marine areas, providing a replicable model for similar regions seeking balanced development.